Influence of HIV/AIDS Care and Support Services Accessibility on Utilization among HIV Infected Adults in Baringo County, Kenya - Danvas Otara; Alex Chebor; Evans Raballah (Evidence-Based Nursing Research)
Context: Globally, efforts are being made to end the HIV/AIDS pandemic and improve the general health of people living with HIV/AIDS through continuous access to care and support services. However, the incidence of dropouts from utilization of HIV care and support services is rising among the HIV-positive clients enrolled in comprehensive care clinics in Baringo County for unidentified reasons. As a result, recognizing the opportunities and challenges in low-resourced communities that must be overcome to promote greater access to care and treatment will influence higher utilization.